Toxic megacolon complicating chemotherapy for acute myeloid leukaemia. - Wodziński, M. A. (BMJ Group, 1994)
A 43 year old woman in remission from acute myeloid leukaemia developed abdominal pain, severe melaena, diarrhoea and gram-negative septicaemia whilst severely pancytopenic following consolidation chemotherapy. Subsequently, serial abdominal X-rays showed a progressive toxic megacolon. Conservative management was attempted but, because of radiological evidence of increasing colonic dilatation and incipient perforation, an emergency defunctioning colostomy was performed. The patient recovered and 2 months later the caecostomy was reversed and a right hemicolectomy performed. This first described case of toxic megacolon following leukaemia treatment is compared with three previously described cases following cytotoxic chemotherapy for other conditions.